Molecular phylogenetics of the sucking louse genus Lemurpediculus (Insecta: Phthiraptera), ectoparasites of lemurs, with descriptions of three new species. (April 2023) - Springer, Andrea; Durden, Lance A.; Kiene, Frederik; Klein, Annette; Rakotondravony, Romule; Ehlers, Julian; Greiman, Stephen E.; Blanco, Marina B.; Zohdy, Sarah; Kessler, Sharon E.; Strube, Christina; Radespiel, Ute
Abstract: Sucking lice live in intimate association with their hosts and often display a high degree of host specificity. The present study investigated sucking lice of the genus Lemurpediculus from six mouse lemur ( Microcebus ) and two dwarf lemur ( Cheirogaleus ) species endemic to the island of Madagascar, considered a biodiversity hotspot. Louse phylogenetic trees were created based on cytochrome C oxidase subunit I (COI), elongation factor 1α (EF1α) and internal transcribed spacer 1 (ITS1) sequences. While clustering according to host species was generally observed for COI and ITS1, suggesting high host specificity of the examined lice, EF1α sequences alone did not distinguish between lice of different Microcebus species, possibly due to rather recent divergence. As bootstrap support for basal tree structure was rather low, further data are necessary to resolve the evolutionary history of louse-mouse lemur associations. Three new species of sucking lice are described: Lemurpediculus zimmermanni sp. Nov. From Microcebus ravelobensis, Lemurpediculus gerpi sp.nov. from Microcebus gerpi, and Lemurpediculus tsimanampesotsae sp. nov. from Microcebus griseorufus . These new species are compared with all known congeneric species and identifying features are illustrated for all known species of Lemurpediculus . Graphical abstract: Image 1 Highlights: Sucking lice ( Lemurpediculus spp.) from mouse and dwarf lemurs were studied. Louse phylogenies were created based on three loci (COI, EF1α, ITS1). Results suggest a high host specificity of sucking lice from mouse and dwarf lemurs. Three new Lemurpediculus species are described.